Political Agreements of The Sultan Salahaddin with Zankien Family - Lana Hayder Jukl; Rabeah Fatah Shikh Mohamad (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
This research is entitled (The Political Agreements of Sultan Salah al-Din with the Zankien Family). It deals with the diplomatic and political attempts made by the Sultan towards unifying and coordinating the Islamic front. At that time, the Islamic world (the Islamic Nation) was in a state of discrimination and division and the Sultan considered himself the guardian of the Islamic world and Muslims. After the death of Nuraddin Mahmood al-Zenki in the year 569 AH / 1173 AD, his son, King Saleh, took his place when he was still young. Salah al-Din al-Ayyoubi tried hard in all peaceful ways, wars and treaties, to gather the Zankiens under the banner of the Ayyoubiya State to fight the Crusaders. At the beginning, he tried to take control of Damascus, then the city of Sinjar and the city of Aleppo, which was of special importance, and the city of Mosul remained, which was of great interest to the Zangids. After three rounds of negotiations, he could manage to bring the city under his authority. The Zankiens were not stingy financially and morally in supporting the Sultan. They were an effective force in all the wars against the Crusaders and their standing behind Salah al-Din led to the unification of capabilities in front of the Crusaders. There were several factors that pushed the two sides to the agreement, which had several impact and results. One of the results was the fulfillment of the Sultan's aspirations and hopes for the unification of Muslims and the liberation of the lands, particularly the city of Jerusalem. The Sultan knew that without such unity his wishes would not be fulfilled. Those agreements paved the way for a great victory and the Sultan was very interested in the agreements